Growth Performance and Hematology of Khao Lamphun Calves with the Implementation of Creep Feeding - Suerphang, C.; Sittiboonma, A.; Sorachakura, C.; Intawicha, P.; Panase, P.; Laorodphan, N.; Dongpaleethun, C.; Chiang, H. I.; Ju, J. C. (Faculty of Animal Science, IPB University, 2025)
The study aimed to evaluate the effect of creep feeding on growth performance and the hematological and biochemical profiles of Khao Lamphun calves. Twenty Khao Lamphun cow-calf pairs were randomly allotted into two treatments: T1, no supplementation of creeping feed (n=10), and T2, with concentrates as creep-feeding (n=10). Production or growth performance was evaluated based on body weight gain (BWG), heart girth (HG), hip height (HH), and body length (BL) throughout the experimentation. By day 120, the final live weight of the creep-fed calves was greater than the non-creep-fed calves, p<0.01). The creep-fed calves also showed a higher average BWG than the non-creep-fed calves. The final body conformation indices, i.e., HG, HH, and BL of the creep-fed calves, were higher than the non-creep-fed p<0.05). The hematological profiles showed no difference in the plasma glucose levels between the two groups. The cholesterol level of the creep-fed calves was higher than the non-creep-fed calves (p<0.05). Similarly, no differences were found in calf's serum biochemical and differential leukocyte profiles between treatment groups. In conclusion, the implementation of creep feeding can lead to improved growth performance and health parameters of Khao Lamphun calves. Therefore, it is recommended as a routine practice to enhance the productivity of Khao Lamphun calves in Thailand and, presumably, in other cattle farms.